Every Seafarer Has a Primary Duty That May Provide the Basis of a Defense in a Personal Injury Action - Geraghty, J Patrick (Journal of Law and Commerce, 2010)
A seafarer injured while in the service of a merchant ocean vessel is accorded three causes of action against his or her employer: 1) Jones Act negligence, 2) the warranty of seaworthiness, and 3) maintenance and cure. The latter two causes of action arise under general maritime law, the first is statutory. This article deals with a defense to a seafarer’s claims for Jones Act negligence and unseaworthiness. This defense, commonly known as the “Primary Duty Rule,” has been restated in numerous variations since its inception. This article examines the history and evolution of the Rule and suggests a restatement of the Rule for continued application in the defense of seafarer personal injury cases.